2009
DOI: 10.2190/hs.39.2.j
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Awareness of and Attitudes toward Gifts from Pharmaceutical Companies to Physicians

Abstract: The purpose of this study was to assess patients' awareness of and attitudes toward physicians' receiving gifts from the pharmaceutical industry. The Alger County Community Health Study was a self-report survey targeting rural Alger County, Michigan. The survey (completion rate 10.1%) addressed issues on health, demographics, and patients' awareness of and attitudes toward gifts to physicians. Rates of awareness of gifts were: drug samples, 94 percent; ballpoint pens, 76.2 percent; medical books, 38 percent; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 23 publications
9
43
1
Order By: Relevance
“…[54] In another study conducted in 1994, the rate of awareness among 486 individuals attending family practice centers varied by type of gift as follows: drug samples (87%); ballpoint pens (55%); medical books (35%); dinner at a restaurant (22%); baby formula (29%); and coffee maker (14%). [52] The third study conducted in 2009 used a similar set of questions as the preceding study, with the following reported rates of awareness among 903 members of the general public: drug samples (94%); ballpoint pens (76%); medical books (38%); dinner out (37%); conference/travel expenses (34%); and golf tournament fees (19%)[59]. …”
Section: Resultsmentioning
confidence: 99%
“…[54] In another study conducted in 1994, the rate of awareness among 486 individuals attending family practice centers varied by type of gift as follows: drug samples (87%); ballpoint pens (55%); medical books (35%); dinner at a restaurant (22%); baby formula (29%); and coffee maker (14%). [52] The third study conducted in 2009 used a similar set of questions as the preceding study, with the following reported rates of awareness among 903 members of the general public: drug samples (94%); ballpoint pens (76%); medical books (38%); dinner out (37%); conference/travel expenses (34%); and golf tournament fees (19%)[59]. …”
Section: Resultsmentioning
confidence: 99%
“…38 One 1995 survey considered the appropriateness of FTs by dollar amount: 9% of patients believed professional gifts should be limited to less than $25 per year, whereas 32% believed that personal gifts should be limited to less than $25 per year (PϽ .001). 35 Three studies (all were of moderate quality or higher) considered patients' views of the acceptability of FTs in research.…”
Section: Acceptability Of Ftsmentioning
confidence: 99%
“…These findings are consistent with those of quantitative research examining patient views on surgeons as industry consultants 25,26 and physician-industry relationships. [27][28][29] In an effort to manage financial relationships between surgeons and device manufacturers, the U.S. Patient Protection and Affordable Care Act mandated public reporting of financial relationships between physicians and pharmaceutical companies and device manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…2 The financial relationships in question included consulting agreements for questionable work, contracts paying royalties without any actual transfer of intellectual property, payments for continuing medical education at exclusive resorts, expensive meals disguised as medical lectures, inappropriate gifts and even direct payments to surgeons for using specific hip or knee implants. 1 After 2 years of investigation, the DOJ filed a criminal complaint on Sept. 27,2007, against 4 of the manufacturers (Zimmer, DePuy, Biomet and Smith and Nephew) for "knowingly and wilfully combining, conspiring, confederating and agreeing with others to commit an offense against the United States by violating the Anti-Kickback Statute." 2 This statute prohibits the exchange of anything of value with the purpose of increasing reimbursement from a federal health program (e.g., Medicare).…”
mentioning
confidence: 99%